Incidences of taillessness in Acanthopagrus arabicus and Oreochromis niloticus collected from the Shatt al-Arab River, Basrah, Iraq - Abed Jassim M.; Jawad Laith A.; Ankush Mujtaba A. (Fisheries & Aquatic Life)
Taillessness (the absence of the caudal fin and some of the caudal peduncle) is described in Acanthopagrus arabicus Iwatsuki and Oreochromis niloticus (L.) specimens collected from the Shatt al-Arab River, Basrah, Iraq. The abnormal specimens completely lacked caudal fins and peduncles. The last remaining caudal vertebra was turned downward in A. arabicus, whereas the remaining parts of the caudal fin skeleton were turned upward in O. niloticus. The abnormalities were assessed by morphological diagnosis. None of the cases was fatal as they occurred in adult individuals. The likely reasons for these abnormalities and the appropriateness of this case study for environmental monitoring are discussed. Additional studies should be conducted from the viewpoint of pollution.